Using Human Milk Fortifiers to Improve the Preoperative Nutritional Status of Infants With Non-restricted Ventricular Septal Defect - Yun-Feng Lin; Yun-Feng Lin; Yun-Feng Lin; Yun-Feng Lin; Wen-Hao Lin; Wen-Hao Lin; Wen-Hao Lin; Shi-Hao Lin; Shi-Hao Lin; Shi-Hao Lin; Qi-Liang Zhang; Qi-Liang Zhang; et al. (Frontiers Media S.A., 2022)
ObjectiveTo explore the effects of human milk fortifier (HMF) on improving the preoperative nutritional status of infants with non-restricted ventricular septal defect (VSD).MethodsA prospective randomized controlled study was conducted in a provincial hospital in China. Participants were randomly divided into an intervention group (n = 29) and a control group (n = 29). HMFs were added proportionally to the infants' feeds in the intervention group based on breastfeeding status, and the infants in the control group received exclusive breastfeeding as needed. The nutritional status of the two groups was compared 1 month after the intervention.ResultsCompared with the control group, the weight, head circumference, height, albumin level, and prealbumin level of the human milk fortifier group were significantly higher 1 month after the intervention (p < 0.05). The STRONGkids score of the HMF group was significantly lower than that of the non-HMF group (p < 0.05). There was no significant difference in pneumonia, liver insufficiency, feeding intolerance, or jaundice between the two groups.ConclusionThe addition of HMFs based on the breastfeeding status of infants with non-restricted VSD can improve the preoperative nutritional status and does not increase the incidence of gastrointestinal complications.Clinical Trial Registrationhttp://www.chictr.org.cn/index.aspx, identifier: ChiCTR2000041135.